How Can Students-centered Classroom Enable Deeper Engagement in a Seventh Grade Course of an ESL Classroom? (2017)
ABSTRACT: The purpose of this AR study was to enable a deeper engagement in a seven grade course of an ESL classroom at the school Miraflores. Aiming to achieve the research goals students-centered classroom was implemented as a key strategy. The data to analyze the impact of this project was collected through teacher journals, check list, video recordings, Ss’ written production, interview, and Ss’ logs. The action plan fostered students’ interactions and helped them to make little contributions to accomplish a given task. Nevertheless, Ss did not use time adequately, did not make considerable efforts to follow instructions at first time, and did not show themselves involved in performing the activities. Key words: Students-centered classroom, group work, scaffolding, engagement.